Extension of the Collective LabourA greement and Minority Union - Toyama Miyagusuku, Jorge (2017)
This paper is about a current Collective Labour Law matter of debate, which is the provenance of the extension of collective labour agreements of minority unions in favor of the non-unionized workers. To start, the authors point the constitutional basis of the Collective Labour Law.Likewise, they refer that exists a strong dualism regarding the acceptance of the extension of the collective agreements signed by a minority union. They arrive to this conclusion after reviewing some of the Peruvian Labour case law, as well as some administrative pronouncements on this field. Finally, they conclude saying that is possible that the collective agreement it be extended, provided that the right of union freedom is not affected.